Optimal tax structures and the problem of double taxation of capital in small and open economies - Díaz H., Fernando (Estudios de Administración, 2001)
The way a country organizes its tax structure can significantly affect the efficiency of capital allocation and can induce sub optimal capital flows. This paper reviews the classical theory of capital international taxation. In the first part an arbitrage model for capital allocation is used to analyze which kind of tax structures lead to interior equilibrium in the international capital market. In the second part the efficiency of such equilibrium and of the tax structures involved are analyzed from the point of view of the maximization of national income. For a small an open economy the optimality of the tax structure strongly depends on the tax structure of its commercial partners and may also depend on the level of the taxes established.